Metachronous, Single Metastasis to the Parotid, from Primary Breast Cancer: A Case Report and Review of the Literature - Michel Kmeid; François G. Kamar; Selim Nasser; Nabil Moukarzel (Case Reports in Oncological Medicine)
Background. The parotid gland is an unusual site for metastatic disease and when metastasis occurs, it commonly originates from head and neck primaries. Spread from distant infraclavicular sites such as the breast, into the parotid, is even more unusual with very few cases reported in the literature. Case Report. We describe the case of a 65-year-old woman presenting for a rapidly enlarging right parotid mass. She had a history of an invasive ductal carcinoma of the right breast and was disease-free in the past 6 years prior to her presentation. She was thereafter diagnosed as having a solitary parotid metastasis from breast origin. A total parotidectomy was done and she was referred for adjuvant radiotherapy. Conclusion. Any parotid metastasis should be investigated, especially in patients with a prior history of cancer where the possibility of metastasis, even if improbable, should be kept in mind. Fine needle aspiration biopsy (FNAB) is the first diagnostic procedure to be done and immunocytochemistry can provide valuable information even if it is not always needed for diagnosis. Superficial parotidectomy when feasible with adjuvant radiotherapy is the preferred approach for solitary metastasis of the parotid. The prognosis, however, remains poor regardless of the treatment modality used.